Answer:
The Answer to the first one is x = 2. Here's an explanation so you can try and solve the others.
Explanation:
First, y = x + 2. Meaning we can substitute the y in 2y. So, we get:
- 4x + 2(x + 2) = 16
- 4x + 2x + 4 = 16 Use distributive property
- 6x + 4 = 16 Add like terms
- 6x + 4 - 4 = 16 - 4 Subtract 4 on both sides of the equation.
- 6x = 12 Divide both sides by 6 to isolate x
- x = 2
For the next equation:
Since both equations equal y, you must put them side by side.
- 3x - 4 = -2x + 6
- 3x - 4 + 4 = -2x + 6 - 4 Subtract 4 on both sides
- 3x = -2x + 2 Add 2x on both sides
- 3x + 2x = 2 Combine like terms
- 5x = 2
- x = 0.4
With the 3rd one just substitute x in 3x with the equation it provides you with (y + 1) and solve (like in the first one).
Same thing with the last one (solve like the second one, side by side), since both equations equal y.
Hope this helps!!